Nocturnal melatonin ingestion improves soccer players` short-term maximal performances on the following day - Ghattassi, K.; Farjallah, M. A.; Graja, A.; Romdhani, M.; Boudhina, N.; Guimard, A.; Driss, T.; Souissi, N.; Chtourou, H.; Hammouda, O. (Research Quarterly for Exercise and Sport, 2024)
Purpose Exogenous melatonin has been proven to have beneficial effects on sleep. A good sleep quality promotes recovery and improves physical performance. In this sense, the present study aimed to explore the potential effect of nocturnal melatonin ingestion on psycho-cognitive and short-term maximal performances, in the following morning.